2005
DOI: 10.1152/ajplung.00134.2004
|View full text |Cite
|
Sign up to set email alerts
|

PKA delivery to the distal lung air spaces increases alveolar liquid clearance after isoproterenol-induced alveolar epithelial PKA desensitization

Abstract: Isoproterenol (Iso) infusion for 48 h in rats decreases the ability of beta-adrenoceptor (beta-AR) agonists to increase alveolar liquid clearance (ALC). An impairment in protein kinase A (PKA) function appears to be critical in producing the desensitized ALC response. To test this hypothesis, we used a novel protein delivery reagent (Chariot, Active Motif) to deliver either the PKA catalytic subunit or the PKA holoenzyme to the distal lung epithelium of Iso-infused rats (400 microg.kg(-1).h(-1), 48 h). After t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 26 publications
(56 reference statements)
4
24
1
Order By: Relevance
“…We investigated whether the restoration of VEGF expression in the null mice would rescue the revascularization to WT levels. For this, we delivered VEGF protein to K IR 6.2 null mice in vivo, post-hind limb ischemia (by Chariot delivery method, see Materials and Methods section) (4,41). Introduction of VEGF in K IR 6.2 -/ -mice restored revascularization to WT levels (Fig.…”
Section: Fig 6 Hif-1a Activation With Ischemia and Its Role In Tubementioning
confidence: 99%
See 1 more Smart Citation
“…We investigated whether the restoration of VEGF expression in the null mice would rescue the revascularization to WT levels. For this, we delivered VEGF protein to K IR 6.2 null mice in vivo, post-hind limb ischemia (by Chariot delivery method, see Materials and Methods section) (4,41). Introduction of VEGF in K IR 6.2 -/ -mice restored revascularization to WT levels (Fig.…”
Section: Fig 6 Hif-1a Activation With Ischemia and Its Role In Tubementioning
confidence: 99%
“…Chariot has been reported to deliver biologically active proteins, peptides, and antibodies directly into cells in vitro and tissues in vivo (4,39,41). Our protocol involved incubation of the Chariot agent with protein (1 lg VEGF/6 ll chariot stock) for 30 min at room temperature followed by injecting it into the ischemic region (between the sutures) about 30 min post-hind limb ischemia and once each day (1 lg/day) thereafter for the next 5 days.…”
Section: Delivery Of Vegf In Vivo (Into the Hind Limb)mentioning
confidence: 99%
“…A major key for successful protein transfer into cells is the development of protein delivery systems with high efficiency and low cytotoxicity (19). Pep-1 as a cell penetrating peptide has been effectively used to transfer different cargoes (peptide nucleic acids or PNAs, peptides, and proteins) into the cells (20)(21)(22)(23)(24)(25)(26)Gros et al,personal communication). Several advantages of the noncovalent complexes of Pep-1/cargo contain: (a) rapid delivery of proteins into cells with high efficiency, (b) stability in physiological buffers, and (c) lack of toxicity and sensitivity to serum.…”
Section: Introductionmentioning
confidence: 99%
“…It involves transient membrane disorganization along with folding of Pep-1 into a helical structure within the phospholipids membrane (27,28). Many types of proteins, antibodies, and peptides were successfully delivered into different cell lines using Pep-1 strategy and were represented to retain their full biological activity (20)(21)(22)(23)(24)(25)(26)Gros et al,personal communication). In this study, the potency of Pep-1 cell penetrating peptide was assessed for HPV16 E7 protein delivery in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Although one study indicated that ENaC can be phosphorylated by PKA (66), the functional relevance of phosphorylation is not yet known and PKA does not activate an amiloride-sensitive current in Xenopus oocytes injected with ENaC mRNAs (67). However, delivery of PKA catalytic subunits to the lung by protein transfection increased the AFC rate in rats (68). ENaC subunits, like other ion channels and transporters, are associated with cytoskeletal proteins such as actin, ankyrin, fodrin, or spectrin, which can serve as signaling molecules.…”
Section: Catecholamine-dependent Regulation Of Alveolar Fluid Clearancementioning
confidence: 99%